Cas9 endonuclease: a molecular tool for in vitro cloning and CRISPR edit detection - Ma, Xingliang; Kthiri, Dhouha; Gill, Manpartik S.; Pozniak, Curtis J.; Kagale, Sateesh (Frontiers in Genome Editing, 2025)
Large genetic engineering constructs often face limitations in DNA element addition or replacement due to lack of unique endonuclease recognition sites. Traditional restriction resistance methods can identify CRISPR-induced mutants efficiently, but CRISPR target sites rarely contain suitable restriction motifs. Here, we demonstrate the use of SpCas9 combined with custom synthesised sgRNAs to linearize large plasmid constructs, enabling DNA element incorporation via seamless cloning methods. Additionally, SpCas9 and custom sgRNAs were used to digest target gene amplicons for effective genotyping of CRISPR-edited mutants, allowing us to distinguish between wild-type, heterozygous, and biallelic variants. This approach provides a straightforward, highly flexible method for modifying large plasmid constructs and screening CRISPR-induced edits.